Tunable lumped-element bandpass filters with constant bandwidth - A. E. Baskakova; V. M. Turgaliev; D. V. Kholodnyak (Известия высших учебных заведений России: Радиоэлектроника)
Lumped-element bandpass filters using LC-tanks and immittance inverters are considered. Tuning of the central frequency is provided by using variable capacitors of LC-tanks and immittance inverters. Tunability of constant-bandwidth bandpass filters is analyzed. Conditions to keep absolute and fractional bandwidth constant are presented. Tunability limitations due to to practical implementation of the immittance inverters and using of real controlling com.ponents (variable capacitors) are discussed. Design of a 3-pole tunable bandpass filter with constant absolute bandwidth is presented.